2021
DOI: 10.14814/phy2.15137
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of myomiR regulation of the pentose phosphate pathway during mechanical load‐induced hypertrophy

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 78 publications
(100 reference statements)
1
11
0
Order By: Relevance
“…A large proportion of downregulated genes were related to oxidative metabolism (Figure 1C) (Table S3). This repressed gene signature could contribute to a "Warburg effect" that occurs during rapid overload-induced muscle hypertrophy, marking a shift towards "aerobic glycolysis" for rapid biomass accumulation (38)(39)(40)(41). Consistent with our prior murine studies (19,25,26) and human resistance exercise time course data (23), Myc was higher after overload (Log2FC=2.0, adj.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…A large proportion of downregulated genes were related to oxidative metabolism (Figure 1C) (Table S3). This repressed gene signature could contribute to a "Warburg effect" that occurs during rapid overload-induced muscle hypertrophy, marking a shift towards "aerobic glycolysis" for rapid biomass accumulation (38)(39)(40)(41). Consistent with our prior murine studies (19,25,26) and human resistance exercise time course data (23), Myc was higher after overload (Log2FC=2.0, adj.…”
Section: Resultssupporting
confidence: 83%
“…MYH2 protein and oxidative fiber proportion increases after prolonged muscle overload (99). MYC-mediated and early Myh2 downregulation during overload may relate to an acute glycolytic preference during rapid hypertrophy (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent publication, the authors confirmed that an overload roughly doubled plantaris glucose uptake, increased lactate secretion by ≈ 50% (but no effect on glycolytic flux) and activated the pentose phosphate pathway as evidenced for example by increased glucose-6 phosphate dehydrogenase protein levels [30]. Moreover, we recently demonstrated that the expression of G6pd, which encodes glucose-6 phosphate dehydrogenase, the rate-limiting gene of the pentose phosphate pathway, is upregulated together with other genes of the pentose phosphate pathway in mechanically overloaded mouse plantaris muscles [31]. The pentose phosphate pathway is active in cancer [32] and synthesises nucleotides for DNA, RNA and ribosome biogenesis (ribosomes primarily consist of ribosomal RNA).…”
Section: Is There Evidence That Metabolicmentioning
confidence: 89%
“…An unbiased RNA interference screen of metabolic genes has identified Phgdh as an enzyme that limits proliferation of breast cancer cells [47]. In muscle, Phgdh expression increases in mouse muscle that hypertrophies after synergist ablation [20,31]. Phgdh expression also transiently increases in response to β 2 -agonist stimulation [48] but not after human resistance exercise [21].…”
Section: Is There Evidence That Metabolicmentioning
confidence: 99%